Thermal analysis in drilling of ex vivo bovine bones - Fernandes, M.G.A. (2018)
Bone drilling is a common procedure in Medicine, mainly in traumatology and orthopedic procedure for fractures fixation and in reconstructive surgery. The success of this surgical procedure is dependent on many factors, namely, on heat generation control during the bone drilling. The main concern in bone drilling is the mechanical and thermal damage of the bone induced by inappropriate parameters such as drill speed and feed-rate during the drilling. This study focuses on the temperature generated during drilling of cortical bone tissue (bovine origin) and solid rigid polyurethane foams with similar mechanical properties to the human bone tissue. Different parameters such as drill speed, feed-rate and hole depth were tested. All results showed that improvement of the drilling parameters and the drill temperatures can be estimated. It was concluded that when the drill speed and feed-rate were higher, the bone temperature increase was lower. The obtained results of temperature in the drilling process of polyurethane foam blocks or bovine bone were compared with a good agreement in between both. © 2017 World Scientific Publishing Company.